PERAN GURU DALAM MENGEMBANGKAN PRILAKU SOSIAL ANAK USIA 5-6 TAHUN - Putri Clawson; Yulia Chitra (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2018)
This study aims to determine how the Role of Teachers in Developing Social Behavior of children (5-6 years old) in RA Anak Bangsa Pekanbaru. The research method used is descriptive. And use a qualitative approach. The subject of this research is the class B2 teacher. The technique used in this study is the technique of observation, interviews, and documentation. Based on the results of research and discussion in this study it can be concluded that the role of teachers in developing social behavior of children aged (5-6 years) in RA Anak Bangsa Pekanbaru can show the development of social abilities possessed by students in RA Anak Bangsa Pekanbaru with the application of right from the teacher's role as a learning resource, manager, facilitator, supervisor, motivator and evaluator. The existence of the stages and factors undertaken also support the application of the teacher's role in developing children's social abilities.